New fluorescence techniques for high-throughput drug discovery. - Jäger, S; Brand, L; Eggeling, C (2003)
The rapid increase of compound libraries as well as new targets emerging from the Human Genome Project require constant progress in pharmaceutical research. An important tool is High-Throughput Screening (HTS), which has evolved as an indispensable instrument in the pre-clinical target-to-IND (Investigational New Drug) discovery process. HTS requires machinery, which is able to test more than 100,000 potential drug candidates per day with respect to a specific biological activity. This calls for certain experimental demands especially with respect to sensitivity, speed, and statistical accuracy, which are fulfilled by using fluorescence technology instrumentation. In particular the recently developed family of fluorescence techniques, FIDA (Fluorescence Intensity Distribution Analysis), which is based on confocal single-molecule detection, has opened up a new field of HTS applications. This report describes the application of these new techniques as well as of common fluorescence techniques--such as confocal fluorescence lifetime and anisotropy--to HTS. It gives experimental examples and presents advantages and disadvantages of each method. In addition the most common artifacts (auto-fluorescence or quenching by the drug candidates) emerging from the fluorescence detection techniques are highlighted and correction methods for confocal fluorescence read-outs are presented, which are able to circumvent this deficiency.